Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Patriot Intan Abadi Di Banjarmasin) - Natasya Fresilia Rahmi; Dwi Wahyu Artiningsih; Periyadi Periyadi (Apik Cahaya Ilmu, 2026)
This research is driven by the importance of employee effectiveness as a critical resource for PT. Patriot Intan Abadi, located in Banjarmasin, which is essential for maintaining production consistency and upholding operational standards amidst a competitive poultry market. The objective of this study is to examine the impact of work discipline and motivation on employee effectiveness. This investigation adopts a quantitative methodology using a survey technique. The participant group consists of 43 employees, all of whom were selected through a census sampling method. Data were evaluated using multiple linear regression facilitated by SPSS software. The results indicate that work discipline has a significant and positive influence on employee effectiveness individually (t-count 3.526 exceeds t-table 2.02). Similarly, work motivation also shows a positive and significant influence on employee effectiveness when considered on its own (t-count 5.540 exceeds t-table 2.02). When viewed collectively, both work discipline and motivation show a substantial positive impact on employee effectiveness (F-count 110.707 exceeds F-table 3.232). The R² value of 0.847 indicates that 84.7% of the variance in employee performance is attributed to work discipline and motivation, while the remaining 15.3% is influenced by additional factors outside the model. The organization should enhance the enforcement of discipline and initiatives to improve motivation in order to maximize employee effectiveness.